2015
DOI: 10.1080/01904167.2014.988356
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic Practices at Low Environmental Impact for Durum Wheat in Mediterranean Conditions

Abstract: 2 The application of conservative agricultural practices such as crop rotation, shallow tillage, and organic fertilizer could usefully sustain crop yield and increase soil fertility, thus playing an important role in the sustainable agriculture. This study was conducted to determine the effects of conservative agronomic practices on yield and quality of wheat. The effects of these practices on soil fertility were further investigated in this four-year study (2005)(2006)(2007)(2008). Two cropping systems, durum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 30 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…However, response of cereals to cultivation in the monoculture varies and is limited by habitat conditions, agrotechnical measures used, and many other factors. The yield of cereals is also affected by tillage systems (Gruber et al 2012;Zikeli et al 2013;Montemurro and Maiorana 2015). Many research works have demonstrated that better production results are achieved in the conventional tillage system on moderately humid soils as well as in the no-tillage system on dry soils or in the years with low sums of precipitation (López-Bellido et al 1996;De Vita et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, response of cereals to cultivation in the monoculture varies and is limited by habitat conditions, agrotechnical measures used, and many other factors. The yield of cereals is also affected by tillage systems (Gruber et al 2012;Zikeli et al 2013;Montemurro and Maiorana 2015). Many research works have demonstrated that better production results are achieved in the conventional tillage system on moderately humid soils as well as in the no-tillage system on dry soils or in the years with low sums of precipitation (López-Bellido et al 1996;De Vita et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…. ) [38,39], research on conservation agriculture, especially on effective practices to adopt and suitable genotypes, would be a good asset to promote this agricultural management technology to farmers in order to encourage them to opt for conservation agriculture. The use, in conservation agriculture, of plant material previously selected in conventional agriculture programs shows limits in terms of genotype performance and reveals contrasting results on several traits [40], hence the need to carry out research and conduct programs that can reassure the farmer of the performance of the varieties that will be proposed for direct seeding.…”
Section: Discussionmentioning
confidence: 99%